Pelatihan Daring Aplikasi Media Sosial dalam Pemasaran Produk Kerajinan Bambu di Selaawi, Garut, Jawa Barat - Santi Susanti; Rachmaniar Rachmaniar; Iwan Koswara (Jurnal Pengabdian Pada Masyarakat, 2020)
ONLINE TRAINING OF SOCIAL MEDIA APPLICATION FOR MARKETING BAMBOO CRAFT PRODUCT IN SELAAWI, GARUT, WEST JAVA. The distribution of goods and services needs marketing to reach the potential customers. The development of internet technology expand the marketing of goods and services from traditional to online market. The bamboo artisans of Selaawi Subdistrict, Garut Regency, realized that it was necessary to market their products online to increase the market share of their craft products, which are currently distributed offline. The Community Service (PPM) Team of Fikom Unpad conducted "Online Training on Social Media Applications for Marketing Bamboo Craft Products in Selaawi, Garut Regency" for creative bamboo economic people in Selaawi Subdistrict, who have not used social media or not optimally used social media as a marketing and promotion channels for bamboo handicraft products. This PPM aims to elevate bamboo artisan’s knowledge in using social media to support the marketing and distribution of bamboo handicraft products directly to customers and sales agents. The social media skills is expected to invite buyers, and increase bamboo artisan’s income. PPM activity presented speakers who owned Amygdala Bamboo, the Head of Selaawi subdistrict, the coordinator of bamboo craft artisans in Selaawi, and PPM Team of Fikom Unpad. This PPM activity was conducted online through Zoom Cloud Meetings, which was attended by bamboo crafts artisans and other participants.